2006
DOI: 10.1097/00001813-200603000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and atrial fibrillation: a rare manifestation of chemotherapy toxicity

Abstract: Gemcitabine is a purine analog with known activity in many solid tumors, namely lung, breast, pancreatic, genitourinary and head/neck cancers. Cardiac toxicity is a rare event and only one report previously described atrial fibrillation (AF) as a consequence of gemcitabine infusion. We report two cases of women suffering from lung cancer who were treated with gemcitabine. Both patients were admitted to hospital for paroxysmal AF occurring 12-24 h after the infusion of the drug. In the first case a sinus rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…There have been reports of atrial flutter and fibrillation in patients treated with gemcitabine [114][115][116][117]. An active metabolite of gemcitabine, 2´,2´-difluorodeoxyuridine, could be responsible for this toxicity [117].…”
Section: Gemcitabinementioning
confidence: 99%
“…There have been reports of atrial flutter and fibrillation in patients treated with gemcitabine [114][115][116][117]. An active metabolite of gemcitabine, 2´,2´-difluorodeoxyuridine, could be responsible for this toxicity [117].…”
Section: Gemcitabinementioning
confidence: 99%
“…Most of these report supraventricular tachycardias including atrial fibrillation 8, 9. Atrial fibrillation is typically seen 18–24 h of infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence increases with age -up to 4% in people over the age of 60 and approximately 9% in people over the age of 80. AF is usually not an immediately life-threatening arrhythmia but produces substantial discomfort and morbidity and may increase mortality, particularly in patients with structural heart disease [9][10][11][12]. AF is often associated with cardiovascular diseases such as heart failure, valvular heart diseases and hypertension as well as thyroid dysfunction and pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Major side effects of the treatment with gemcitabine are hepatic dysfunction, myelosuppression, renal impairment, problems during concurrent radiotherapy (gemcitabine is a strong radiosensitizer) and pulmonary toxicity [14]. Recently, Ferrari et al [10] have reported on 2 patients who developed AF under gemcitabine therapy. They suggested that gemcitabine, and specifically its deaminated metabolite dFdU, could have a direct effect on the myocardial cells and the conduction system, evoking overstimulation of the sinoatrial node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation